Hubungan Antara Riwayat Status Gizi Ibu Masa Kehamilan Dengan Risiko Stunting Anak Balita Di Puskesmas Pintuangin Kota Sibolga Tahun 2023 - Remensiwaty Simorangkir; Magdalena Br Barus (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2023)
Maternal nutrition during pregnancy is very important for the growth of the fetus she is carrying. The mother's nutritional status during pregnancy greatly influences the child's growth. This study aims to determine the relationship between the history of nutritional status of mothers during pregnancy and the risk of stunting in children under five at the Pintuangin Health Center, Sibolga City in 2023. This type of survey is with a cross sectional design, namely explaining the relationship between History of maternal nutritional status during pregnancy with the risk of stunting of children under five at the Pintuangin Health Center, Sibolga City in 2023. The population in this study were mothers with toddlers who visited the Pintuangin Health Center, Sibolga City, The sampling technique used consecutive sampling technique. Data were analyzed using the square test. Based on the research results, there is a relationship between nutritional status history and the risk of stunting with a p-value of 0.002 and a PR of 6.5. It is hoped that parents can prepare for health from pregnancy to birth, especially consuming foods that contain balanced nutrition. Maintain the health of toddlers, try to provide a variety of foods that contain nutrients according to needs.